Long-Term Health Outcomes of Korean Adults With Classic Congenital Adrenal Hyperplasia Due to 21-Hydroxylase Deficiency - Lim, Seung Gyun; Lee, Young Ah; Jang, Han Na; Kong, Sung Hye; Ahn, Chang Ho; Kim, Sang Wan; Shin, Choong Ho; Kim, Jung Hee (Frontiers in Endocrinology, 2021)
There is a lack of studies regarding the long-term outcomes of Asian adults with classic congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency. We hypothesized that adults with CAH are at higher metabolic risk than their age-, and sex-matched controls. We further investigated the long-term health outcome-related factors in adults with CAH. We compared metabolic risk between adults with CAH (71 men, 93 women) and age-, and sex-matched controls (190 men, 261 women) from the Korean National Health and Nutrition Examination Survey data. The presence of obesity, testicular adrenal rest tumors (TARTs), and menstrual irregularity was assessed. Hormone status and treatment regimens were compared according to the presence of adverse outcomes. The median age was 27.0 y and 28.0 y for men and women, respectively. Adults with CAH had a higher waist circumference (88.0 vs. 82.3 cm in men, and 83.5 vs. 72.3 cm in women), and blood pressure (125.0 vs. 113.0 mmHg in men, and 120.0 vs. 104.0 mmHg in women) than age- and sex-matched controls (P<0.05 for all). The 2.7-fold increased risk for hypertension (men) and 2.0-fold increased risk for obesity (women) was significant in patients with CAH (P<0.05 for both). Obese adults with CAH showed significantly higher adrenal limb thicknesses (men) and 17-hydroxyprogesterone and dehydroepiandrosterone sulfate levels (women) (P<0.05 for both). TARTs occurred in 58.1% of men and did not differ by hormone or treatment regimen. Irregular menstruation was observed in 57.1% of women, with higher dehydroepiandrosterone sulfate levels in those with irregular periods. Adults with CAH had a higher metabolic risk than the general population. Poor disease control may increase their risk of metabolic morbidity and menstrual irregularity.